Unmagnetized plasma media parameters reconstruction using FDTD and gradient‐based minimization method - Deng, Haochuan; Shi, Lijuan; Feng, Xuejian; Wei, Xiao; Yin, Hongcheng (International journal of numerical modelling, 2020)
A time‐domain inverse scattering algorithm for determining unknown plasma resonance frequency and electron collision frequency of unmagnetized plasma media object has been proposed. Finite‐difference time‐domain (FDTD) method in conjunction with Lagrange multipliers and gradient‐based minimization method are used in the proposed algorithm. The reconstruction of the parameters is based on the minimization of a cost function that describes the discrepancy between simulation and measured data of the electric field at the observation points. In order to obtain the gradient value of the unknown plasma parameters, an augmented cost function has been given by means of Lagrange multipliers with the Maxwell curl equations and constitutive relation of the unmagnetized plasma media. Then, the gradient value could be obtained after a series of transformations. At last, the Ploak‐Ribiere conjugate gradient algorithm has been applied to update the plasma parameters iteratively. The effectiveness of the proposed algorithm has been validated through the simulation test.